A Study on the perceptions of the University of the Philippines-Diliman students and head librarians on coffee shops in the UPD libraries - Manuel, Melyssa Lauren M. (2011)
Many libraries abroad have installed coffee shops or coffee carts in their libraries for the convenience of their patrons and to attract more users. This research, entitled "A Study of the Perceptions of University of the Philippines - Diliman Students and Head Librarians On Coffee Shops in the UPD Libraries," aims to determine the probable effectiveness of adapting this concept in the local setting. In particular, it focused on collecting and differentiating data on the perceptions of chosen University of the Philippines Diliman students and head librarians about coffee shops and coffee vending machines inside or in the vicinity of the UPD libraries. The chosen libraries were the College of Law Library, the Main Library, the College of Mass Communication Library, and the College of Engineering Libraries. A total of 200 students - 50 students from each library - answered the survey, and five head librarians were interviewed.